Study of the compressive and tensile strenghts of self-compacting concrete with sugarcane bagasse ash - MOLIN FILHO,R. G. D. (2019)
Abstract In this work, the axial compressive strength at 3, 7 and 28 days of age and the tensile strength at 28 days of age of specimens of two self-compacting concrete (SCC) compositions were evaluated. The difference between them was the presence of the sugarcane bagasse ash (SCBA) in the substitution rate of 10% of the sand mass in the second trace. The traces were developed based on the rheological parameters of the NBR 15823 Brazilian standard. The strengths at 28 days were evaluated by the confidence interval of the Student’s t-test with α of 5%. The results in the fresh state have proved that the rheological performances between the SCC’S are similar. Moreover, the SCC with SCBA obtained equivalent performances in the compressive and tensile strengths at all ages when compared to the SCC without SCBA, with an effective reduction of 87 Kg of sand per cubic meter of concrete.